ADULT GRANDCHILD SUPPORT PROVIDED TO GRANDPARENTS. (11th November 2018) - Beaulieu, C; Kim, K; Huo, M; Zarit, S; Fingerman, K
Abstract: Previous research on support exchanges between generations focuses on support from middle-aged children to older parents and from grandparents to young grandchildren. However, when the grandchildren are grown up, they may become a source of support for their grandparents. The current study examined support adult grandchildren provided to their grandmother and grandfather, and factors that are associated with the support given. Adult grandchildren (N = 495; Mage = 27.92) from the second wave of the Family Exchanges Study (2013) reported how often they provided support to each grandparent (N = 358; Mage = 80.89). Multilevel models were estimated to predict support provided to grandparents, using grandchildren's, grandparents', and the middle generation's characteristics. On average, support to the grandmother was given approximately a few times a year, while support to the grandfather was closer to yearly. Higher levels of both positive and negative relationship quality were associated with more support given to each grandparent. In addition, when the middle generation (grandchild's parents) provided help to the grandparents, the grandchild was also likely to provide more support to both grandmother and grandfather. The amount of support the grandchild provided was limited, but the support was associated with relationship and family characteristics (e.g., relationship quality and support from the middle generation), but not their demographic characteristics. Findings provide evidence for solidarity theory in families with parents providing care to grandparents. This also suggests a need to consider family characteristics for better understanding grandparent-grandchild ties and support exchanges in adult families for future research.